Antibacterial activity of taro [Colocasia esculenta (L.) Schott] leaves extract against foodborne pathogens and its effect on microbial population in raw chicken meat - Mohammad Khamees, Alzabt Abdal Rahman; Rukayadi, Yaya (Rynnye Lyan Resources, 2021)
Chicken meat is one of the most consumed animal products worldwide. It is a favourable medium for bacterial growth due to its high moisture content and nitrogenous compounds. The growth of foodborne pathogens in food products can cause food poisoning and foodborne illness. Chemical preservatives act to restrict microbial growth which causes deterioration and spoilage of chicken meat and chicken meat products. Chemical preservatives, however, are not preferred nowadays due to consumer perception and their residual effect on the human body. Therefore, the interest in the development of plantbased bio preservatives as a natural alternative to chemical preservatives is increasingly gaining attention. This study aimed to evaluate the antimicrobial activity of taro [Colocasia esculenta (L.) Schott] leaves extract against foodborne pathogens, including Escherichia coli ATCC 43895, Listeria monocytogenes ATCC 19112, Salmonella enterica serovar Typhimurium ATCC 14028, and Staphylococcus aureus ATCC 29737, as well as its effect on microbial population in chicken meat at different concentrations and exposure times. Taro leaves powder was extracted by maceration methods using ethanol as a solvent. The crude extract was tested for antibacterial activity by means of disc diffusion assay (DDA), minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-kill curve analysis. The effects of the extract on microbial population were evaluated at different concentrations, exposure times and storage temperatures. The results showed the inhibition zone of the extract against tested bacterial ranged from 9.5±0.3 mm to 11.6±0.2 mm. The extract can inhibit the growth and kill the tested bacteria with MIC and MBC of 2.50 and 5.00 mg/mL, respectively. The time-kill curve analysis demonstrated that the extract can completely kill the tested bacteria at 4× MIC for 0.5 hrs. Approximately, 5% of the extract could reduce all the microbial population in chicken meat samples with an exposure time of 30 mins. The result suggested that taro leaves extract (TLE) can be integrated into the food system as a natural food preservative.